EFFICIENCY OF THE USE OF GRAPHIC PROGRAMS (AUTOCAD, COMPASS, CORELDRAW) IN HIGHER TECHNICAL EDUCATION - Saidnazarova Saida Fakhritdinovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In connection with the widespread introduction of computer technologies into science and industry, the question arises of the need for students to acquire skills in this direction. The graphic training of students of technical directions forms the basis of engineering education. Professional competence in many disciplines involves the development of computer graphics by students. Teaching the computer graphics section is focused on using the AutoCAD graphic editor to form the professional qualities of future specialists. When conducting practical classes, the student's activities include the execution of the task in the manual version and the subsequent execution of drawings in the computer-aided design system using 2D and 3D modeling. The article presents some aspects of the work on the implementation of computer technologies in the educational process.